2016
DOI: 10.3390/atmos7050071
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Seasonal Climatic Anomalies on Zoo Visitation in Toronto (Canada) and the Implications for Projected Climate Change

Abstract: Abstract:This study uses a multi-year temporal climate analogue approach to explore zoo visitor responses to seasonal climatic anomalies and assess the impacts of projected climate change on zoo visitation in Toronto, Canada. A new method for selecting a representative weather station was introduced which ranks surrounding stations based on "climatic distance" rather than physical distance alone. Two years representing anomalously warm temperature conditions and two years representing climatically normal tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The parameter estimates can be obtained by finding the parameter values maximizing Equation (8), in other words, applying the maximum likelihood estimation method. All the estimates for the two parameters, α and β, are statistically significant at the 1% level.…”
Section: Estimation Results Of the Oohb DC Spike Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameter estimates can be obtained by finding the parameter values maximizing Equation (8), in other words, applying the maximum likelihood estimation method. All the estimates for the two parameters, α and β, are statistically significant at the 1% level.…”
Section: Estimation Results Of the Oohb DC Spike Modelmentioning
confidence: 99%
“…Martin [7] reported that the climate has a role as a facilitator, making tourism activities enjoyable. Hewer and Gough [8] explored and assessed zoo visitors' responses to seasonal climatic anomalies. Scott and Lemieux [9] explained that the tourism demand is motivated by certain climate and weather information.…”
Section: Introductionmentioning
confidence: 99%
“…Time, which is often a proxy for population growth and zoo expansion, has also been shown to result in increased zoo attendance in Toronto [5,6], the UK [4], and Taiwan [10]. Furthermore, previous studies in Toronto [9] and Taiwan [10] have also identified the positive effect of "animal stars" and other special attractions on zoo attendance, along with the negative effect of external events, such as disease epidemics, political instability, and competing events. It is therefore important to consider the potentially confounding effects of non-climatic factors in any tourism climatology study which examines the effects of weather and climate variability on human participation.…”
Section: Introductionmentioning
confidence: 95%
“…The next series of tourism climatology papers that focused on zoo attendance emerged from the United States, looking at thermal comfort for the Phoenix and Atlanta zoos [7], as well as the effect of synoptic weather systems for the Atlanta and Indianapolis zoos [8]. Another tourism climatology paper that examined zoo attendance was conducted by Hewer and Gough [9], which looked at the effect of seasonal climatic anomalies on attendance at the Toronto Zoo (Toronto, ON, Canada). Interestingly, both the Pekins and Debbage [7] and the Hewer and Gough [9] papers were published as part of the last special issue on tourism climatology in the MDPI journal Atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation